Análise de polimorfismos dos genes DGAT1 e LEP no desempenho produtivo em bovino leiteiro da raça Girolando - Cardoso, Shirleny Romualdo (2008)
CHAPTER 2: Candidate genes have been associated with milk production in bovines, such as the diacylglycerol O-acyltransferase 1 (DGAT1) and leptin (LEP); however, they have not been simultaneously investigated nor have been evaluated in the Brazilian Girolando breed (Gir × Holstein, backcrossed to Holstein). Our aim was to determine the influence of fat-related genes, DGAT1 and LEP, and their polymorphisms on performance traits of milk production in the Girolando breed. Results indicated that the K allele of the DGAT1 gene showed a significant association with total and average daily milk production with additive effect. The LEP gene showed that the A allele and its homozygote are highly prevalent and almost fixed in this population and may have been favorably selected during backcrossing for the origin of this breed. The important impact of the K allele of the DGAT1 gene on milk production corroborates the initiative of performing marker-assisted selections with this gene in breeding programs of the Girolando breed.